Taxonomic notes on Protoperidinium (Peridiniales, Dinophyceae) species in the Thermaikos Bay (North Aegean Sea, Greece) - EVAGELOPOULOS, A. (Mediterranean Marine Science, 2002)
The thecal morphology and plate pattern of fourteen species of the genus Protoperidinium, found in the inner Thermaikos Bay (North Aegean Sea, Eastern Mediterranean) during the period 1989-1992, are described and discussed. These species are: P. depressum, P. oceanicum, P. oblongum, P. claudicans, P. punctulatum, P. conicum var. concavum ?, P. cf. obtusum, P. sp., P. brochi, P. divergens, P. curtipes, P. oviforme, P. pallidum and P. diabolus. Among the fourteen species, P. cf. obtusum and P. sp. are the most interesting from a taxonomic point of view. The morphology of the theca of each species combines features attributed in the current literature to two different species, P. obtusum and P. leonis. These features concern primarily the shape of the 1’ plate and the morphology of the hypotheca. As a consequence of my findings, I believe that the morphology of the 1’ plate and the sculpture of the epitheca may be too variable to be used to distinguish between P. obtusum and P. leonis. We also believe that P. obtusum, P. leonis as well as P. striatum require further clarification of their diagnostic characters. Taxa of similar morphology to P. sp. have been recorded in the literature and they may represent a new Protoperidinium taxon.